Targeted covalent inhibitors of MDM2 using electrophile-bearing stapled peptides. Issue 55 (21st June 2019) - Charoenpattarapreeda, Jiraborrirak; Tan, Yaw Sing; Iegre, Jessica; Walsh, Stephen J.; Fowler, Elaine; Eapen, Rohan S.; Wu, Yuteng; Sore, Hannah F.; Verma, Chandra S.; Itzhaki, Laura; Spring, David R.
Abstract : An electrophile-bearing linker was developed for the generation of a stapled peptide covalent inhibitor of MDM2 via a two-component CuAAC peptide stapling. Abstract : Herein, we describe the development of a novel staple with an electrophilic warhead to enable the generation of stapled peptide covalent inhibitors of the p53–MDM2 protein–protein interaction (PPI). The peptide developed showed complete and selective covalent binding resulting in potent inhibition of p53–MDM2 PPI.